2021
DOI: 10.3390/app11041735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cell-Free miR-205-5p, let-7f-5p, and miR-483-5p Expression in Ovarian Cell Cultures and Plasma Samples of Patients with Ovarian Cancer

Abstract: The term liquid biopsy reveals a non-invasive diagnostic method that might be based on the quantification of cell-free microRNAs in body fluids. However, the identification of candidates for liquid biopsy is challenging. Our aim was to compare the cell-free expression of miR-483-5p, miR-205-5p, and let-7f-5p in ovarian cell cultures and plasma samples of patients with ovarian cancer. Both the intracellular and cell-free expression of miR-205-5p and let-7f-5p proved to be higher in the Estrogen Receptor α (ERα)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…The ERα-positive PEO1 cell line and the A2780 cell line that does not express ERα [ 18 ]. According to our previous studies, ERα expression strongly influenced the basal expression of miRNAs in these cell lines [ 18 , 19 ]. Based on the above findings, we further investigated the basal expression of miR-30a-3p, miR-30a-5p, miR-30d-5p, and miR-30e-5p in the PEO1 and A2780 cell lines.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The ERα-positive PEO1 cell line and the A2780 cell line that does not express ERα [ 18 ]. According to our previous studies, ERα expression strongly influenced the basal expression of miRNAs in these cell lines [ 18 , 19 ]. Based on the above findings, we further investigated the basal expression of miR-30a-3p, miR-30a-5p, miR-30d-5p, and miR-30e-5p in the PEO1 and A2780 cell lines.…”
Section: Resultsmentioning
confidence: 92%
“…These results suggest that miR-30s—especially miR-30a-5p and miR-30d-5p—might have higher biological relevance in the ERα-expressing PEO1 cell line. We also determined whether the expression of miR-30s change in response to estrogen exposure, a phenomenon that was observed in the case of some miRNAs in our previous studies [ 18 , 19 ]. In these experiments, the PEO1 cell line was treated with E2 in a 10 nM–100 µM concentration range.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, the diagnostic potential of microRNA-34a and microRNA-31 is analogous to combined microRNA panels for the early diagnosis of EOC. Recent study showed combined diagnostic value of miR-34a and CA-125 could discriminate EOC from normal with an AUC of 0.818, while lower expression of let-7f has the diagnostic value of AUC 0.78 [ 24 29 30 31 32 ]. Moreover, the comparative expression analysis of let-7f in different cancers (colorectal, lung, prostate, papillary thyroid cancer) showed a higher diagnostic value for discriminating respective cancer from the normal [ 29 31 32 33 34 35 ].…”
Section: Discussionmentioning
confidence: 99%